Penggunaan Media Powerpoint Interaktif Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Yudi Budianti; Rima Rikmasari; Dita Aditya Oktaviani (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This research is motivated by low student learning outcomes. This is because some teachers consider this learning media to be less important, and still use conventional learning media. This study aims to describe the use of interactive PowerPoint media on the learning outcomes of elementary school students. The research method used is Systematic Literature Review (SLR) with the following procedures: (1) Formulate research questions (problem formulation) related to the title; (2) Conduct a search for journal data/Literature Systematic Review (enter keywords into the journal search database); (3) Conduct screening and selection for research journals that are following research problems; (4) The data used is then analyzed; (5) Conducts a critical review of the journals used to see the suitability of the relevant journal criteria; (6) The data has been analyzed, then concluded so that be a conclusion regarding SLR; and (7) Make a final report of the SLR research. The sample for the analysis is 9 published journal articles published in the 2013-2022 range. Based on the classification of journal articles divided into, the research method is 6 Classroom Action Research (PTK) journals and 3 Experimental journals, then based on the lower-class and upper-class categories, and based on subject analysis. It can be concluded that the use of interactive PowerPoint media can improve student learning outcomes in teaching and learning activities, help eliminate boredom, and motivate student learning.